Erratum: MIRAB-BALOU, M., HU, Q.L., FENG, J.N. & CHEN, X.X. (2011) A new species of Sericothripinae from China (Thysanoptera: Thripidae), with two new synonyms and one new record. Zootaxa, 3009, 55–61. - Mirab-Balou, M.; Hu, Q. L.; Feng, J. N.; Chen, X. X. (Zootaxa, 2011)
One new species of subfamily Sericothripinae (Thysanoptera: Thripidae) is described and illustrated: Hydatothrips longjingensis sp. n., and H. abdominalis (Kurosawa) is newly recorded from China. The following taxonomic changes are established: Sericothrips houji (Chou & Feng) comb. n. (from Hydatothrips).